Artikel ini mengulas kegiatan Ed Edukasi Stop Bullying & Perundungan Di SMP N 10 Bengkulu Utara : Upaya Membangun Kesadaran Siswa dalam Mewujudkan Lingkungan Sekolah yang Aman dan Inklusif - Agil nugraha, Muhamad (Jurnal INDONESIA RAYA (Pengabdian pada Masyarakat Bidang Sosial, Humaniora, Kesehatan, Ekonomi dan Umum), 2025)
Bullying is a serious issue that frequently occurs in school environments, including junior high schools. This behavior can cause negative impacts on victims, both physically, psychologically, and socially. Therefore, concrete efforts are needed to prevent and address bullying through structured educational activities. The program “Stop Bullying & Harassment Education at SMP Negeri 10 Bengkulu Utara” was conducted as a form of socialization and awareness-raising among students regarding the dangers and consequences of bullying. The materials provided included an understanding of the definition of bullying, its types, contributing factors, and strategies for prevention within the school environment. In addition, the program emphasized the important role of teachers, peers, and families in creating a safe, comfortable, and child-friendly school atmosphere. Through a participatory approach, students were engaged in discussions, educational video screenings, and interactive games aimed at fostering empathy and mutual respect. The results indicated an increase in students’ understanding of the dangers of bullying, along with a growing collective commitment to building a bullying-free school. It is expected that this educational initiative will help SMP Negeri 10 Bengkulu Utara become a model school in reducing bullying cases and in establishing a positive, harmonious, and supportive learning environment for holistic student development. Keywords:Bullying, Harassment, Education, SMP Negeri 10 Bengkulu Utara, Prevention